TV is business a descriptive study - Rasos, Marco Angelo Javier 1978-
Television has always been perceived as an information source, an entertainer, a public servant and the watchdog of society. Little do people realize that TV is primarily a business. The TV industry has already been in the country for years now yet very few studies on its business side have been done. This study has been conceived to shed light on the nature of TV stations as business entities and to describe how TV stations conduct business. In order to get first hand information on what is going on inside the TV stations, interviews were conducted with the Finance Heads and Finance Representatives of TV stations ABS-CBN, PTV, ABC, GMA, RPN and IBC. This study compared and analyzed the revenues, the expenses, the profits, the disbursement systems and budget making channels of the six VHF TV stations in the country. Results proved that TV is indeed a business. Figures showed that the industry is generating large amounts of revenues from the sale of advertising spots. As a whole it is also spending a lot on labor, maintenance of equipment, acquisition of equipment and production expenses. Data also revealed that the stations employed similar procedures in their money disbursement and budget making systems. This study concludes that the TV business industry is big, growing, competitive and profitable. It is highly recommended that further studies on media economics be conducted.